Quality of Life After Fractional Flow Reserve–Guided PCI Compared With Coronary Bypass Surgery. Issue 22 (2nd April 2022) - Fearon, William F.; Zimmermann, Frederik M.; Ding, Victoria Y.; Zelis, Jo M.; Piroth, Zsolt; Davidavicius, Giedrius; Mansour, Samer; Kharbanda, Rajesh; Östlund-Papadogeorgos, Nikolaos; Oldroyd, Keith G.; Wendler, Olaf; Reardon, Michael J.; et al.
Abstract : Background: Previous studies have shown that quality of life improves after coronary revascularization more so after coronary artery bypass grafting (CABG) than after percutaneous coronary intervention (PCI). This study aimed to evaluate the effect of fractional flow reserve guidance and current generation, zotarolimus drug-eluting stents on quality of life after PCI compared with CABG. Methods: The FAME 3 trial (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) is a multicenter, international trial including 1500 patients with 3-vessel coronary artery disease who were randomly assigned to either CABG or fractional flow reserve–guided PCI. Quality of life was measured using the European Quality of Life–5 Dimensions (EQ-5D) questionnaire at baseline and 1 and 12 months. The Canadian Cardiovascular Class angina grade and working status were assessed at the same time points and at 6 months. The primary objective was to compare EQ-5D summary index at 12 months. Secondary end points included angina grade and work status. Results: The EQ-5D summary index at 12 months did not differ between the PCI and CABG groups (difference, 0.001 [95% CI, –0.016 to 0.017]; P =0.946). The trajectory of EQ-5D during the 12 months differed ( P <0.001) between PCI and CABG: at 1 month, EQ-5D was 0.063 (95% CI, 0.047 to 0.079) higher in the PCI group. A similar trajectory was found for the EQ (EuroQol) visual analogue scale. The proportion of patients with Canadian Cardiovascular Class 2 or greater angina at 12 months was 6.2% versus 3.1% (odds ratio, 2.5 [95% CI, 0.96–6.8]), respectively, in the PCI group compared with the CABG group. A greater percentage of younger patients (<65 years old) were working at 12 months in the PCI group compared with the CABG group (68% versus 57%; odds ratio, 3.9 [95% CI, 1.7–8.8]). Conclusions: In the FAME 3 trial, quality of life after fractional flow reserve–guided PCI with current generation drug-eluting stents compared with CABG was similar at 1 year. The rate of significant angina was low in both groups and not significantly different. The trajectory of improvement in quality of life was significantly better after PCI, as was working status in those <65 years old. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02100722.